Knee and ankle biomechanics with lateral wedges with and without a custom arch support in those with medial knee osteoarthritis and flat feet. Issue 9 (5th February 2016) - Hatfield, Gillian L.; Cochrane, Christopher K.; Takacs, Judit; Krowchuk, Natasha M.; Chang, Ryan; Hinman, Rana S.; Hunt, Michael A.
ABSTRACT: This study compared immediate changes in knee and ankle/subtalar biomechanics with lateral wedge orthotics with and without custom arch support in people with knee osteoarthritis and flat feet. Twenty‐six participants with radiographic evidence of medial knee osteoarthritis (22 females; age 64.0 years [SD 8.0 years], BMI 27.2 kg/m 2 [4.2]) and flat feet (median foot posture index = + 5) underwent three‐dimensional gait analysis for three conditions: Control (no orthotic), lateral wedge, and lateral wedge plus arch support. Condition order was randomized. Outcomes included frontal plane knee and ankle/subtalar biomechanics, and comfort. Compared to the control, lateral wedge and lateral wedge with arch support reduced the knee adduction moment impulse by 8% and 6%, respectively ( p  < 0.05). However, the lateral wedge resulted in a more everted foot position (4.3 degrees) than lateral wedge plus arch support (3.2 degrees) ( p  < 0.05). In contrast, lateral wedge plus arch support reduced foot frontal plane excursion compared to other conditions ( p  < 0.05). Participants self‐reported significantly more immediate comfort with lateral wedge plus arch support compared to the control, whereas there was no difference in self‐reported comfort between lateral wedge and control. No immediate changes in knee pain were observed in any condition. Clinical significance: Rather than prescribing lateral wedges to all patients with knee osteoarthritis, those who have medial knee osteoarthritis and flat feet may prefer to use the combined orthotic to reduce loads across the knee, and to minimize the risk of foot and ankle symptoms as a consequence of orthotic treatment. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1597–1605, 2016.